A new species of the endemic Australian genus Hyptiogaster Kieffer Hymenoptera: Gasteruptiidae) - Parslow, Ben A.; Jennings, John T. (Zootaxa, 2018)
Hyptiogaster arafura sp. nov. is described from Arafura Swamp, Northern Territory, Australia, as the eleventh species of Hyptiogaster Kieffer (Hymenoptera: Gasteruptiidae). A revised diagnosis of Hyptiogaster is given based on the new species.